The Characteristics And Financial Performance Of Local Governments In Indonesia: The Moderating Role Of Financial Health Level - Firmansyah, Amrie; Arfiansyah, Zef; Huda, Arifudin Miftakhul (Universitas Negeri Semarang, 2024)
Purpose: This study examines the effect of capital expenditure and the level of dependency on the financial performance of local governments in Indonesia. This study also includes the level of financial soundness as a moderating variable. Method: This study uses local government financial data throughout Indonesia from www.djpk.kemenkeu.go.id. This study produced a total sample of 630 observations based on purposive sampling. Hypothesis testing was done using multiple linear regression analysis for cross-section data. Findings: This study concludes that capital expenditure has a positive effect on local government financial performance, while the level of dependency has a negative effect on local government financial performance. In addition, the level of financial soundness does not increase the positive relationship between capital expenditure and local government financial performance. The level of financial soundness also does not reduce the negative relationship between the level of dependency and the financial performance of local governments. Novelty: This study employs local government’s financial health as a moderating variable in the influence of capital expenditure and the level of dependence on local government financial performance in this study, which is still rarely conducted in previous studies. Also, this research contributes to providing literature related to local government financial health, which is rarely reviewed in the field of public sector accounting in Indonesia.